Who does what: A novel tool to rapidly assess intra-household participation in agriculture and food-related tasks - Kumar, Neha (International Food Policy Research Institute, 2023)
There are many steps needed to get food on plates— all of which take resources and time. Yet we do not know how different household members are contributing their time. Neither do we have simple tools to measure their contributions to household tasks in household surveys. The aim of the current study is to develop and test a tool to understand how household tasks—ranging from agricultural to food preparation and care activities—are allocated across household members. Using data from about 5,000 households in five districts across India, Bangladesh and Nepal, we explore how task allocation varies with the sex and age of the household members and identify gender gaps in task sharing within the household. We find that, across the three countries, agricultural tasks are shared among household members, with men engaged in a large number of tasks and women supporting in a few tasks. For tasks related to food preparation, we observe that men are primarily involved in purchasing foods and everything else is done by women (and girls). Unlike standard time-allocation modules that typically interview one or two members of a household, our approach enables us to map what each household member is contributing. The findings will deepen our understanding of how food is prepared and consumed, which is essential to develop feasible and sustainable solutions for healthy diets in South Asia.